Adjuvant chemotherapy with or without bevacizumab in patients with resected non-small-cell lung cancer (E1505): an open-label, multicentre, randomised, phase 3 trial. Issue 12 (December 2017) - Wakelee, Heather A; Dahlberg, Suzanne E; Keller, Steven M; Tester, William J; Gandara, David R; Graziano, Stephen L; Adjei, Alex A; Leighl, Natasha B; Aisner, Seena C; Rothman, Jan M; Patel, Jyoti D; Sborov, Mark D; et al.
Summary: Background: Adjuvant chemotherapy for resected early-stage non-small-cell lung cancer (NSCLC) provides a modest survival benefit. Bevacizumab, a monoclonal antibody directed against VEGF, improves outcomes when added to platinum-based chemotherapy in advanced-stage non-squamous NSCLC. We aimed to evaluate the addition of bevacizumab to adjuvant chemotherapy in early-stage resected NSCLC. Methods: We did an open-label, randomised, phase 3 trial of adult patients (aged ≥18 years) with an Eastern Cooperative Oncology Group performance status of 0 or 1 and who had completely resected stage IB (≥4 cm) to IIIA (defined by the American Joint Committee on Cancer 6th edition) NSCLC. We enrolled patients from across the US National Clinical Trials Network, including patients from the Eastern Cooperative Oncology Group–American College of Radiology Imaging Network (ECOG-ACRIN) affiliates in Europe and from the Canadian Cancer Trials Group, within 6–12 weeks of surgery. The chemotherapy regimen for each patient was selected before randomisation and administered intravenously; it consisted of four 21-day cycles of cisplatin (75 mg/m 2 on day 1 in all regimens) in combination with investigator's choice of vinorelbine (30 mg/m 2 on days 1 and 8), docetaxel (75 mg/m 2 on day 1), gemcitabine (1200 mg/m 2 on days 1 and 8), or pemetrexed (500 mg/m 2 on day 1). Patients in the bevacizumab group received bevacizumab 15 mg/kg intravenously every 21 days starting with cycle 1 of chemotherapy and continuing for 1 year. We randomly allocated patients (1:1) to group A (chemotherapy alone) or group B (chemotherapy plus bevacizumab), centrally, using permuted blocks sizes and stratified by chemotherapy regimen, stage of disease, histology, and sex. No one was masked to treatment assignment, except the Data Safety and Monitoring Committee. The primary endpoint was overall survival, analysed by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT00324805 . Findings: Between June 1, 2007, and Sept 20, 2013, 1501 patients were enrolled and randomly assigned to the two treatment groups: 749 to group A (chemotherapy alone) and 752 to group B (chemotherapy plus bevacizumab). 383 (26%) of 1458 patients (with complete staging information) had stage IB, 636 (44%) had stage II, and 439 (30%) had stage IIIA disease (stage of disease data were missing for 43 patients). Squamous cell histology was reported for 422 (28%) of 1501 patients. All four cisplatin-based chemotherapy regimens were used: 377 (25%) patients received vinorelbine, 343 (23%) received docetaxel, 283 (19%) received gemcitabine, and 497 (33%) received pemetrexed. At a median follow-up of 50·3 months (IQR 32·9–68·0), the estimated median overall survival in group A has not been reached, and in group B was 85·8 months (95% CI 74·9 to not reached); hazard ratio (group B vs group A) 0·99 (95% CI 0·82–1·19; p=0·90). Grade 3–5 toxicities of note (all attributions) that were reported more frequently in group B (the bevacizumab group) than in group A (chemotherapy alone) were overall worst grade (ie, all grade 3–5 toxicities; 496 [67%] of 738 in group A vs 610 [83%] of 735 in group B), hypertension (60 [8%] vs 219 [30%]), and neutropenia (241 [33%] vs 275 [37%]). The number of deaths on treatment did not differ between the groups (15 deaths in group A vs 19 in group B). Of these deaths, three in group A and ten in group B were considered at least possibly related to treatment. Interpretation: Addition of bevacizumab to adjuvant chemotherapy did not improve overall survival for patients with surgically resected early-stage NSCLC. Bevacizumab does not have a role in this setting and should not be considered as an adjuvant therapy for patients with resected early-stage NSCLC. Funding: National Cancer Institute of the National Institutes of Health.